Analisis Produk Layanan Rawat Inap di RSUD Wangaya Denpasar Berdasarkan STP (Segmenting, Targeting, Positioning) dan 4 P (Product, Price, Place, Promotion) - Wahyuni, Ni Putu Sri (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
Service marketing strategy will increase the level of customer satisfaction with marketing mix consisting of 4 P (product, price, place, promotion) and supported by modern STP marketing strategies (Segmenting, Targeting and Positioning) as a technique to look for market opportunities, so that the hospital is able to provide health services according to customer needs. Descriptive research has been conducted to describe a situation objectively, to solve the problem being faced. The data used are secondary data that includes inpatient visit data, occupancy data for inpatient rooms, and community satisfaction data in inpatient rooms. Based on the results of the study, obtained information that Marketing strategy with the concept of segmentation, target and position and supported by the right marketing mix is an effective means to improve health services according to customer needs. Them, it can be concluded that the marketing strategy at the Regional Hospital of Wangaya Denpasar is quite good, this can be seen from the response of inpatients quite positive because it has received an explanation of the type of service, service procedures and cost information from the hospital